Karakteristik Ibu Hamil dengan Kejadian Ketuban Pecah Dini (KPD) dI RSIA Husada Bunda Tahun 2021 - Milda Hastuty; Dumasari Lubis; Riani Riani; Sri Hardianti (Poltekkes Kemenkes Padang, 2022)
Maternal and perinatal mortality rates remain high worldwide with up to 99% of maternal deaths due to problems in labour or the postpartum period. Maternal mortality in developing countries is highest at 450/100,000 births, compared to developed countries. Premature rupture of membranes is defined as rupture of membranes before the date of birth. It can occur late in pregnancy or before delivery. Under normal circumstances, 8-10% of pregnant women experience premature rupture of membranes. The purpose of this study was to determine the characteristics of pregnant women with the incidence of KPD at Husada Bunda Hospital in 2021. This type of research is descriptive analytic with a cross sectional study design carried out on pregnant women at RSIA Husada Bunda. A total of 126 respondents of the age of pregnant women who were not at risk were 26 respondents experiencing BPH, 118 respondents who were not anaemic in pregnant women were 24 respondents experiencing BPH and 204 respondents of parity who were not at risk were 42 respondents experiencing BPH. Based on the results of the study it can be concluded that there is an incidence of KPD at Husada Bunda Hospital which occurs KPD is 46 people (20.6%). It is hoped that health workers can provide knowledge about KPD to pregnant women when mothers do ANC and mothers know the characteristics of KPD so that KPD does not occur.